The AI Spring of 2018. Issue 3 (29th May 2018) - Olhede, Sofia; Wolfe, Patrick
Abstract: As nations race for dominance in the field of artificial intelligence, Sofia Olhede and Patrick Wolfe consider the implications for statistics and statisticians